Im Streit um die Nutztierhaltung: Gesellschaftsorientierte Kommunikationsstrategien für die Agrar- und Ernährungswirtschaft; Conflicts about Livestock Farming: Societal-oriented Communication Strategies for the Agri-Food Industry - Winnie Isabel Sonntag; Manuel Ermann; Achim Spiller; Marie von Meyer-Hof̈er (German Journal of Agricultural Economics (GJAE), 2021)
– Farmers as well as the agricultural and food industry are confronted with increasingly diverse social requirements regarding livestock farming. In this context, there are environmental and climate protection concerns, but especially the living conditions of the animals are criticized. In addition to the questions of how animal husbandry systems should be developed and how this can be financed, different communicative levels of discussion can be observed. So far, there has been little systematic research concerning the question which communication strategies might be successful. This research gap is addressed in this conceptual paper. Communication strategies from the literature are systematized in a new conceptual way and are illustrated and discussed using practical examples from the agricultural and food industry. Furthermore, practical support is given to choose, apply and evaluate socially oriented communication strategies. This includes a stronger consideration of dialogue-oriented communication processes that combine elements of trust marketing and value discourses.
Keywords: 330; Public Relations; Landwirtschaft; Vertrauen; Nachhaltigkeit; Innovation